PARTISIPASI MASYARAKAT KOTA BERBASIS MANFAAT DALAM MEMBENTUK TAMAN PUBLIK RAMAH ANAK - Utami, Putri Kharisma; Mugnisjah, Wahju Qamara; Munandar, Aris (Jurnal Lanskap Indonesia, 2016)
Child-friendly public park is a form of urban outdoor space that beneficial not only for citizen in general but also beneficial for child’s needs in urban spaces. Urban environment around children, including community in it gives great influence to the existence of child-friendly public spaces. Therefore, study on community participation in establishing park that promotes child-friendly public park is proper to conduct. This study focuses on investigating response from user that benefits from city park development project called Ruang Publik Terpadu Ramah Anak (RPTRA), a project developed by Jakarta municipality to promotes integrated community outdoor activities that is friendly for children’s growth and development needs. Result from using questionaire and interview method shows reliability of user is sufficient (Cronbach’s Alpha > 0.600) in showing relation between space variables in child-friendly public parks and response from community as beneficiary user.